HUBUNGAN UMUR KEHAMILAN, DISTOLIK DAN DIASTOLIK TERHADAP SINDROM HELLP PADA IBU HAMIL DENGAN PRE EKLAMSIA BERAT DI RS MARGONO SOEKARJO PURWOKERTO - ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The most common maternal disorder in pre-eclampsiacases is hellp's syndrome. Hellp's syndrome is characterized by intravascular haemolysis,elevated levels of hepatic enzymes and coagulation system. The diagnosis of hellpsyndrome is characterized by a decrease in platelet levels <100,000 / mm3, elevated liverenzymes; LDH> 600 IU / dl, SGOT> 70 IU / dl. Help syndromes affect the mother,among others, can cause placental abruption, DIC, acute renal failure, pulmonaryedema, whereas in infants can cause respiratory disturbance and fetal growth disorders.Factors affecting hellp syndrome include age, paritÄs, gestational age, blood pressure.Objective: To determine the relationship between gestational age, systolic pressure, anddiastolic pressure with hellp syndrome in pre-eclampsia mother. Methods: This studyused descriptive analytic. The total population of 103 pregnant women with preeclampsiainMargonosoekardjoHospitalPurwokerto,withpurposivesamplesthatmeetthe criteria of inclusion and exclusion to 42 people. Univariate and Bivariate dataanalysis using chi square test with degree of confidence p = 0,05. The results showed thatmost ofÂ  pregnant women with preelamsia had a term of aterm pregnancy, systolicpressure greater than 160 mmHg, and diastolic pressure less than 110 mmHg, and norelationship between gestational age, systolic pressure and diastolic pressure to theoccurrence of hellp syndrome In pregnant women with pre-eclampsia.Keywords: gestational age, systolic, diastolic, hellp syndrome